ANALYSIS OF RISK FACTORS SUNTING IN CHILDREN AGED 0-24 MONTHS IN BANYUMAS REGENCY - Wati, Erna Kusuma; Setiyowati, Rahardjo; MAQFIROCH, ARRUM FIRDA AYU (Kesmas Indonesia, 2025)
Stunting is a chronic malnutrition problem. Stunting mainly occurs in the first 1000 days of life (0-23 months) and continues until the age of five. The purpose of the study was to analyze the risk factors for stunting in children aged 0-24 months in Banyumas Regency. Observational research design with cross sectional design, 8 months research duration. The sample in this study was 100 children aged 0-24 months, using cluster random sampling technique. Research variables included gender, history of breastfeeding, history of infectious disease, parenting, number of family members, mother's age, parenting, education and nutritional knowledge of the mother. Bivariate data analysis using chi square test to determine the relationship of risk factors The results showed that 42.0% of children aged 0-24 months experienced stunting. Risk factors for stunting in children 0-24 months of male gender (p: 0.017), breastfeeding (p: 0.036), history of infectious disease in the last month (p: 0.047), and large number of family members p: 0.019). In an effort to reduce the incidence of stunting in children aged 6-24 months, it is necessary to increase breastfeeding until 24 months of age and prevent children from suffering from infectious diseases, especially diarrhea and acute respiratory infections